Ten years of myocutaneous flaps for pressure ulcers in patients with spinal lesions: Analysis of complications in the framework of a specialised medical-surgical pathway. Issue 11 (November 2018) - Lefèvre, Chloë; Bellier-Waast, Frédérique; Lejeune, Florence; Duteille, Franck; Kieny, Pierre; Le Fort, Marc; Perrouin-Verbe, Brigitte
Abstract: Introduction: The objective of the study is to analyse complications associated with surgery for pelvic pressure ulcers in terms of their frequency, nature and rate of surgical revisions. The secondary aims are to analyse the rate of recurrence, length of stay and time to healing, and to determine factors associated with complications and recurrence. Methods: It is a single-centre, retrospective cohort study with a 10-year follow-up setting in Nantes University Hospital, France, a specialist centre for spinal cord injury (SCI). All patients who were admitted to the Neurological Physical Medicine and Rehabilitation (PMR) department for surgery (flap coverage) for pelvic pressure ulcers between 1st of January 2004 and 30th September 2014 were included. The main outcome measures were the rate of complications, rate of recurrence, length of stay and time to healing, as well as factors associated with complications and recurrence. Results: One hundred and sixty-six patients underwent 252 flap procedures in 239 operations. The majority of patients had SCI (78.3%). The ulcer sites were mainly ischial (67%), sacral (20%) and trochanteric (12%). Gluteus maximus was used most often (75.3% of flaps) (ischial and sacral ulcers), followed by tensor fascia lata (16.2%) (trochanteric ulcers). The rate of complications that delayed return to wheelchair at 6 weeks was 34.5%. The factors associated with complications were more than one surgical ulcer and drainage time greater than 10 days. The rate of recurrence was 20.04%. The factors related to recurrence were young age, scoliosis and an oblique pelvis. Conclusions: Management within a specialised medical-surgical pathway limited post-operative complications and recurrences in this sample of subjects who mostly had SCI.